Alternativas de base nanotecnológica en el control de etileno y/o actividad antimicrobiana para mejorar la vida poscosecha del aguacate Hass (2022)
Avocado ripening and many of its quality parameters are influenced by ethylene production and pathologies such as anthracnose, whose management represents a challenge for the industry since they affect the commercialization of this fruit. An alternative to control ethylene production is the use of nanoparticles with photocatalytic behavior that inhibit ethylene production through reactions. Thus, in this work, TiO2 particles doped with different concentrations of Ag were synthesized by the self-combustion technique in solution. The obtained particles were subjected to their respective morphological characterization using techniques such as XRD and SEM. Agglomerates of TiO2 particles were obtained in anatase phase, with 0.75%, 1.5% and 3.5% mol Ag of approximately 109.5 nm and in mixed anatase-ruthyl phase with 0% and 4.5% mol Ag with average sizes of 184.03 and 205.06 nm. The presence of Ag was confirmed by EDS, and through FTIR assays the bonds associated with the obtained material were identified (O-H and Ag interactions, Ti-O vibrations, O-H narrowing). The particle size distribution analysis and BET analysis, allow concluding that as the average agglomerate size decreases, there is an increase in the surface area, which is an important element for the photocatalytic activity. It was found that TiO2 particles with 0.75% mol Ag were the ones that presented the best response and therefore, they were taken as a reference to perform ethylene removal tests, antifungal activity and simulated transport tests. The presence of TiO2 particles doped with Ag enabled ethylene removal, antifungal activity and a delay in the ripening process of Hass avocado when in contact with the material.